2021
DOI: 10.1177/0272989x211003589
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine Hesitancy and Differential Susceptibility to Media Coverage: A Critical Documentary Led to Substantial Reductions in Human Papillomavirus Vaccine Uptake in Denmark

Abstract: Objectives To investigate whether negative media coverage of the human papillomavirus (HPV) vaccine led to a decrease in the uptake of the first dose of the HPV vaccine (HPV1) in Denmark and, importantly, whether some groups of individuals were more susceptible to negative media coverage. Methods We measured HPV vaccine uptake of 12-year-old girls born in 2001 to 2004 using Danish administrative data. A quasi-experimental design was employed to assess whether a documentary that was critical of the HPV vaccine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…11 Female children born prior to 2001 have coverage rates close to 90 percent at one and three years after the recommended vaccination date. However, for children born in the 2001-2005 period, the coverage rate drops sharply and reaches a minimum of 10 percent at age 13 for children born in 2004 (with a recommended vaccination date in 2016).12 As other studies have documented, the drop in HPV coverage was closely linked to extensive media coverage of suspected severe side-e ects from the vaccine, including a critical television documentary airing in March 2015(Gørtz et al, 2020;Humlum et al, 2021). When those claims were refuted by the health authorities, coverage rates increased again and plateaued at around 70 percent prior to the 2019 reminder reform.These general patterns in vaccination coverage over time set the stage for our study of the e ectiveness of reminder letters.…”
mentioning
confidence: 98%
“…11 Female children born prior to 2001 have coverage rates close to 90 percent at one and three years after the recommended vaccination date. However, for children born in the 2001-2005 period, the coverage rate drops sharply and reaches a minimum of 10 percent at age 13 for children born in 2004 (with a recommended vaccination date in 2016).12 As other studies have documented, the drop in HPV coverage was closely linked to extensive media coverage of suspected severe side-e ects from the vaccine, including a critical television documentary airing in March 2015(Gørtz et al, 2020;Humlum et al, 2021). When those claims were refuted by the health authorities, coverage rates increased again and plateaued at around 70 percent prior to the 2019 reminder reform.These general patterns in vaccination coverage over time set the stage for our study of the e ectiveness of reminder letters.…”
mentioning
confidence: 98%
“…This intuition is based on a simple two-good world, with good 1 being vaccination of child 1 and good 2 being vaccination of child 2 and vaccinations being normal goods. The introduction of the vaccination program corresponds to a decrease in the price of good 1 in this world.22 Fitzpatrick and Thornton (2018) provide evidence from Nicaragua on how households change their health utilization in response to a health insurance program that implies di↵erential coverage across family members.23 Appendix TableA.6 shows estimated direct and spillover e↵ects by mother's characteristics; earnings quartile, education level, health care education and age at childbirth.24 Existing studies have also demonstrated that high-SES families are more likely to be adherent to health recommendations or informational interventions(Suppli et al, 2018;Lübker and Lynge, 2019; Oster, 2020;Humlum et al, 2021).…”
mentioning
confidence: 99%